Magnetically Controlled Soft Robotics Utilizing Elastomers and Gels in Actuation: A Review. (9th December 2020) - Chung, Hyun‐Joong; Parsons, Andrew M.; Zheng, Lelin
Abstract : A magnetic field has unique advantages in controlling soft robotics inside of an enclosed space, such as surgical catheters or untethered drug‐delivering robots operating in the human body. Soft actuators, made of elastomers and gels functionalized with magnetically active materials, are natural choices to drive magnetically controlled motions of soft robots. Recent innovations in soft material technologies, including 3D printing, origami/kirigami, tough hydrogels, mechanical metamaterials, and liquid metal‐injected elastomers, offer technological foundations to develop soft actuators and robots with significantly enhanced performance. Herein, an overview of magnetic soft actuators and robots from a materials engineer's perspective is provided. First, the historical background and recent trends of magnetic soft actuators are discussed. Second, the motions of tethered or untethered magnetic soft robotics are classified into aquatic swimmers, terrestrial locomotors, and grippers. Herein, preprogrammed motion under patterned magnetic stimuli is achieved by controlled magnetization of elastomeric materials containing hard magnetic particles. Finally, the applications of magnetically controlled soft robotics in surgical and therapeutic medical devices are discussed. Abstract : Recent breakthroughs in magnetically controlled soft actuators and soft robotics are highlighted herein. However magnetically controlled soft robotics draw attention as a potential tool for minimally invasive surgery and targeted drug delivery, technological developments in materials fabrication are reviewed in the context of the recent innovation on magnetically steered swimmers, terrestrial crawlers, grippers, and smart surgical devices.